Risk Factors for Temporary Vascular Access Infection in Patients with End-Stage Renal Disease Undergoing Hemodialysis in Cipto Mangunkusumo Hospital - Adityo Susilo; Kresna Dharma Suryana; Pringgodigdo Nugroho; Muhadi Muhadi; Beryl Alodia; Leonard Nainggolan (Acta Medica Indonesiana, 2022)
Background: Temporary vascular access is used to provide adequate hemodialysis for patients who are initiating dialysis or are awaiting maturation of a more permanent vascular access. However, infection is one of the most frequent complications of using temporary vascular access and is the second leading cause of death in patients undergoing hemodialysis after cardiovascular events. There has been no research on the risk factors for the incidence of infection in patients using temporary vascular access in Indonesia. Methods: This is a retrospective cohort study utilizing secondary data from medical records of 318 subjects aged 18 years and older with end-stage renal disease and undergoing hemodialysis using temporary vascular access at Cipto Mangunkusumo Hospital. Results: Temporary vascular access infection was found in 125 of 318 subjects (39.3%). The risk factors of temporary vascular catheter infection in the multivariate analysis were females (OR 1.731; 95% CI 1.050-2.854; p=0.032), low hemoglobin levels (OR 2.293; 95% CI 1.353-3.885; p=0.002), presence of diabetes mellitus (OR 2.962; 95% CI 1.704-5.149; p<0.001) and duration of catheter insertion (OR 5.322; 95% CI 1.871-15-135; p=0.002). The association between ferritin and catheter insertion site was not analyzed as a risk factor because it was not performed in all subjects. Conclusion: The incidence of infection in patients with end -stage renal disease undergoing hemodialysis using temporary vascular access at Cipto Mangunkusumo Hospital was 39.3%. Female gender, low hemoglobin level, diabetes mellitus, and duration of catheter insertion were risk factors for temporary vascular access infection.